Factors influencing international students intention in choosing banks in Malaysia - Ahmed, Nur Mohamoud Ahmed (2015)
The number of international students studying in Malaysian institution of higher education is continuously growing. The vast numbers of international students in Malaysia has contributed not only to the country’s education sector, but the banking industry as well. Thus, the purpose of the study is to examine the factors influence international student's intention to choose a bank. This study focuses on all international students in Northern State of Malaysia, particularly three public universities, namely University Utara Malaysia, University Sains Malaysia and University Malaysia Perlis. A total of 150 questionnaires are distributed and 141 usable responses were received. The result of the study shows that 60 percent of the variance of international student's intention to choose banking system can be explained by the independent variables which are attitude, subjective norm, religiosity, trust and knowledge. However, out of the five independent variables, the variable, namely attitude, subjective norm and religiosity are found significant to the intention to choose bank, while the other two variables, which are trust and knowledge are not significant